2017
DOI: 10.48550/arxiv.1711.01511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of Sustained >100 MeV Gamma-ray Emission Associated with Solar Flares

G. H. Share,
R. J. Murphy,
A. K. Tolbert
et al.

Abstract: We characterize and provide a catalog of thirty >100 MeV sustained γ-ray emission (SGRE) events observed by Fermi LAT. These events are temporally and spectrally distinct from the associated solar flares. Their spectra are consistent with decay of pions produced by >300 MeV protons and are not consistent with electron bremsstrahlung. SGRE start times range from CME onset to two hours later. Their durations range from about four minutes to twenty hours and appear to be correlated with durations of >100 MeV SEP … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…The Large Area Telescope (LAT) on board the Fermi γ-ray Space Telescope (Fermi : Atwood et al 2009) has increased the number of observed solar flares with photon emission above 100 MeV by an order of magnitude compared to all previous instruments (Share et al 2017). One prominent characteristic of these flares is the long-duration emission extending hours past the impulsive phase, long after other flare associated electromagnetic emissions at longer wavelengths have decayed (e.g., Ajello et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Large Area Telescope (LAT) on board the Fermi γ-ray Space Telescope (Fermi : Atwood et al 2009) has increased the number of observed solar flares with photon emission above 100 MeV by an order of magnitude compared to all previous instruments (Share et al 2017). One prominent characteristic of these flares is the long-duration emission extending hours past the impulsive phase, long after other flare associated electromagnetic emissions at longer wavelengths have decayed (e.g., Ajello et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Sun is a bright source of multi-GeV γ-rays, with emission observed both from its halo -due to cosmic-rays electrons interacting with solar photons -and its disk -due to hadronic cosmic rays (mostly protons) interacting with solar gas. (Emission from solar particle acceleration is only bright during flares and has not been observed above 4 GeV [1][2][3][4][5][6][7][8].) Although the halo emission [9] agrees with theory [10][11][12], the disk emission does not, and hence is our focus.…”
mentioning
confidence: 99%
“…In addition to the preliminary analysis in Ack17 mentioned at the outset, there have been similar determination of electron spectra based on HXRs (Share et al 2017;Plotnikov et al 2017) assuming both thin and thick-target, based only on electron energy spectra, and without consideration of the energy dependence of the escape time. As expected the electron indexes derived in these papers are different than those presented here, which not only are for a thin target model but also include the energy dependence of the escape time.…”
Section: Combined Electron Spectramentioning
confidence: 98%